Treatment of purulent wounds the patients with phlegmons of the maxillofacial area and neck - Тимофеев, Алексей Александрович; Умиров, Александр Владимирович; Мирошник, Антон Александрович; Дубиченко, Сергей Игоревич (Actual Dentistry, 2019)
Purpose: to determine the effectiveness of the use of the antiseptic solution «Octenisept» in complex for the treatment of purulent wounds the patients with phlegmons of the maxillofacial area and neck. Methods: A clinical examination of 38 patients with phlegmons of the maxillofacial area and neck was conducted. Results. On the basis of the conducted examinations of patients with phlegmons of the maxillofacial area and neck, it was objectively proved that the antiseptic antiseptic solution «Octenisept» used for the local treatment of purulent wounds has a pronounced antiseptic effect, which is much higher than that of traditional antiseptic agents (chlorhexidine). Conclusions. In patients with phlegmons of the maxillofacial area and neck, the antiseptic solution «Octenisept» may be recommended for the local treatment of purulent wounds in order to prevent the development of terrible inflammatory complications. Key words: purulent wounds, phlegmon, purulent-inflammatory diseases, octenisept, chlorhexidine.